Evaluation of Intravenous immunoglobulin usage pattern in an educational hospital, a descriptive-cross sectional study, Bandar Abbas, IRAN - Motahareh Ahmadi; Omid Safa; Abd Nazemi; Bahram Doorandish; Fahimeh Gharaie Pour; Maryam Montaseri (Shiraz University of Medical Sciences, 2019)
Introduction: The goal of DUE is to improve patients' care. Studying the administration and utilization pattern of IVIg is an important research topic due to its significant role in the treatment and control of many disorders, high prices, and limited availability. We aimed to evaluate the pattern of IVIg use in an educational hospital. Material and methods: In this descriptive-cross sectional and retrospective study, 250 patients' records included medical orders, nursing notes and drug chart were studied. We used FDA and UK protocol to evaluate of IVIg indications in our study. Data were analyzed using SPSS software. Results: Prescription of IVIg in our hospital adhered to FDA- approved indications and red indications of UK guideline with 64.1% and 67.6%, respectively. ITP was the most common cause of the correct prescriptions (52.7% based on FDA guideline and 50% based on UK guideline). Sepsis (15.5%), hyperbillirubinemia (10.4%), encephalitis (3.5%), and aplastic anemia (1.38%) were incorrect indications of IVIg in our study. ADRs was observed in 14.5% of patients. Discussions: Consumption of IVIg in our hospital, was more consistent with international guidelines compared with other hospitals in IRAN, of course unnecessary prescriptions cannot be ignored. We suggest to develop own national guideline and educate our prescribers to minimize irrational prescription of expensive and important medicines such as IVIg.